The Oral Presentation Competency in Nursing Students of Ardabil University of Medical Sciences in Iran - Tahmineh Rahmatkhah; Rajab Dashti Kalantar; Nazila Vosoghi; Alireza Mirzaei; Saeed Mehri (Iran University of Medical Sciences, 2023)
Background & Aims Oral presentation skills play an important role in the personal, academic and professional success. It is the most common method of educational assessment in higher education settings. This study aims to determine the oral presentation competency of nursing students from Ardabil university of medical sciences (AUMS). Materials & Methods This is a descriptive cross-sectional study that was conducted in 2023 on 274 nursing students from AUMS, who were selected using a convenience sampling method. The data collection tool were a demographic form and Chiang's oral presentation evaluation scale (OPES). The collected data were analyzed in SPSS software, version 20, using independent t-test and one-way analysis of variance. Results The total score of OPES was 58.81±7.75. The scores of the dimensions of accuracy in content, effective communication, and clarity of speech was 4.01±0.348, 3.72±0.658, and 4.02‌±‌0.673, respectively. Competency was higher in Persian speaking students than in Azari-speaking students. Also, students with a history of more oral presentation and reading of public speaking books obtained higher scores. Conclusion Considering the importance of oral presentations for nurses, it is recommended that nursing professors in AUMS and the educational system in Iran pay more attention to promote this skill in Azeri-speaking nursing students.